Celiac Disease in Children and YouTube: Do the Videos Contain Accurate Information? - Abdulkerim Elmas; Mustafa Akcam (Turkish Archives of Pediatrics)
Objective: Celiac disease (CD) is a gluten-associated enteropathy whose incidence has been increasing in recent years. Parents whose children are diagnosed with CD search for information about the disease via the internet. YouTube is one of the most frequently used platforms to access information due to the number of users and ease of access. This study aims to investigate how much quality and reliable information the most frequently viewed videos contain for families seeking information about celiac disease in children via YouTube.